KEPERCAYAAN, CUSTOMER RELATIONSHIP MANAGEMENT DAN KEPUASAN TERHADAP LOYALITAS PELANGGAN DI CV. PRISCA JAYA ABADI - Prisca Eris Anjarwati; Udik Jatmiko; Kukuh Harianto (Commodities, Journal of Economic and Business, 2023)
The problem addressed in this research is the phenomenon of declining customer loyalty at CV Prisca Jaya Abadi, which specializes in selling reinforced steel products. The issue is indicated to be influenced by trust, customer relationship management, and satisfaction. The objective of this research is to identify and explain the partial and simultaneous effects of trust, customer relationship management, and satisfaction on customer loyalty. The research approach used is quantitative, with a population of 42 customers and the sampling method used is saturation sampling. The data analysis techniques used in this research are descriptive analysis and inferential statistics, including validity and reliability tests, classic assumption tests, multiple linear regression tests, t-tests, and F-tests. The research findings show that the regression equation Y = 3.289 + 0.245 X1 + 0.144 X2 + 0.769X3. Partially, the trust variable has a significant effect on customer loyalty, with a t-value of 4.629 > t-table of 2.108, and a significant value of 0.003 < 0.05. The customer relationship management variable has no significant effect on customer loyalty, with a t-value of 1.217 < t-table of 2.108, and a significant value of 0.231 > 0.05. The satisfaction variable has a significant effect on customer loyalty, with a t-value of 6.168 > t-table of 2.108, and a significant value of 0.000 < 0.05. Simultaneously, trust, customer relationship management, and satisfaction have a significant effect on customer loyalty at CV Prisca Jaya Abadi in Kediri, as proven by an F-value of 35.706 and a significant F-significance of 0.000 < 0.05.